Bicolour painting of the Descartes products - Zelenyuk, E. G.; Malykhin, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 1990)
We shall color the Cartesian product ω ´ ω_1 with two colors. Can an infinite subset Aω and an uncountable subset Bω_1 be found such that the product A´B can be one-colored? This problem proves to be unsolvable in ZFC.